Greenland high-elevation mass balance: inference and implication of reference period (1961–90) imbalance. Issue 70 (2015) - Colgan, William; Box, Jason E.; Andersen, Morten L.; Fettweis, Xavier; Csathó, Beáta; Fausto, Robert S.; Van As, Dirk; Wahr, John
Abstract: We revisit the input–output mass budget of the high-elevation region of the Greenland ice sheet evaluated by the Program for Arctic Regional Climate Assessment (PARCA). Our revised reference period (1961–90) mass balance of 54±48 Gt a –1 is substantially greater than the 0±21 Gt a –1 assessed by PARCA, but consistent with a recent, fully independent, input–output estimate of high-elevation mass balance (41±61 Gt a –1 ). Together these estimates infer a reference period high-elevation specific mass balance of 4.8±5.4 cm w.e. a –1 . The probability density function (PDF) associated with this combined input–output estimate infers an 81% likelihood of high-elevation specific mass balance being positive (>0 cm w.e. a –1 ) during the reference period, and a 70% likelihood that specific balance was >2 cm w.e. a –1 . Given that reference period accumulation is characteristic of centurial and millennial means, and that in situ mass-balance observations exhibit a dependence on surface slope rather than surface mass balance, we suggest that millennial-scale ice dynamics are the primary driver of subtle reference period high-elevation mass gain. Failure to acknowledge subtle reference period dynamic mass gain can result in underestimating recent dynamic mass loss by 17%, and recent total Greenland mass loss by 7%.